THE EFFECT OF PRICE DISCOUNTS ON CUSTOMER SATISFACTION WITH IN STORE DISPLAY AS AN INTERVENING VARIABLE - Irada Sinta; Rico Nur Ilham; Muhammad Multazam; T.M Azani; Ikram (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
In this study the population is Rizky Net Bandar Masalam customers, Simalungun Regency. i.e. 50 people. Because the target population is less than 100, the sampling technique used is the census method, where the entire population of 50 Rizky Net Customers in Bandar Masilam, Simalungun Regency, will be used as the research sample. the first hypothesis is accepted, meaning that price discounts (X) have a significant effect on In Store Display (Y1). the second hypothesis is accepted, meaning that price discounts (X) have a significant effect on customer satisfaction (Y2). the third hypothesis is accepted, meaning that In Store Display (Y1) is an intervening variable that mediates the effect of Discounts (X) on Customer Satisfaction (Y2).